Eksplozja ćmysłów, implozja słowa. Primum Mobile Zenona Fajfera - Bloch, Irmina (Przestrzenie Teorii, 2024)
The article talks about Zenon Fajfer’s kinetic poem titled Primum Mobile, published in the volume ten letters in 2010, which is a new attempt to find a different kind of literacy, postulated by futurists – and in particular corresponding to the need to exceed the limits set by the book. However, in this case (exceptionally) total literature does not focus on materiality (at least not in its form), but “happens” electronically. It is some kind of looking at pure movement, at what drives emotions, what gives energy to the word. Fajfer opens the poem by placing his Primum Mobile in the poetic punctum, in the dot above the i, represented as a black square on a white background, and thus the supremacist atom of art. The author pays particular attention to the figure of the “moth-senses” as a way of experiencing, based on visual-tactile perception, associated with the desire to annihilate, i.e. with ekpyrosis. The article, in addition to the analysis of Fajfer’s work, deals with liberatic visions of freeing words, the search for a new book and the fear of the crisis of the letter as what drives the imperative of movement in a liberatic work.